Care Navigation Increases Initiation of Hepatitis C Treatment After Release From Prison in a Prospective Randomized Controlled Trial: The C-LINK Study. (28th July 2022) - Papaluca, Timothy; Craigie, Anne; McDonald, Lucy; Edwards, Amy; Winter, Rebecca; Hoang, Annabelle; Pappas, Alex; Waldron, Aoife; McCoy, Kelsey; Stoove, Mark; Doyle, Joseph; Hellard, Margaret; et al.
Abstract: Background: Prison-based hepatitis C treatment is safe and effective; however, many individuals are released untreated due to time or resource constraints. On community re-entry, individuals face a number of immediate competing priorities, and in this context, linkage to hepatitis C care is low. Interventions targeted at improving healthcare continuity after prison release have yielded positive outcomes for other health diagnoses; however, data regarding hepatitis C transitional care are limited. Methods: We conducted a prospective randomized controlled trial comparing a hepatitis C care navigator intervention with standard of care for individuals released from prison with untreated hepatitis C infection. The primary outcome was prescription of hepatitis C direct-acting antivirals (DAA) within 6 months of release. Results: Forty-six participants were randomized. The median age was 36 years and 59% were male. Ninety percent ( n = 36 of 40) had injected drugs within 6 months before incarceration. Twenty-two were randomized to care navigation and 24 were randomized to standard of care. Individuals randomized to the intervention were more likely to commence hepatitis C DAAs within 6 months of release (73%, n = 16 of 22 vs 33% n = 8 of 24, P < .01), and the median time between re-entry and DAA prescription was significantly shorter (21 days [interquartile range IQR, 11–42] vs 82 days [IQR, 44–99], P = .049). Conclusions: Care navigation increased hepatitis C treatment uptake among untreated individuals released from prison. Public policy should support similar models of care to promote treatment in this high-risk population. Such an approach will help achieve hepatitis C elimination as a public health threat. Abstract : We demonstrated that postprison release transitional care, using a care navigator model, is associated with a higher likelihood of hepatitis C DAA initiation among individuals who are released untreated. Treatment was also initiated earlier after release compared with unsupported individuals.